Freshwater fishes of the Río de la Plata: current assemblage structure - Maiztegui, Tomás (2022)
Few studies have addressed the composition of fish assemblages of the freshwater Río de la Plata (RdlP) and have only been limited to species lists gathered over the last two centuries. As such inventories have never been reviewed or validated by fish sampling, the richness and structure of RdlP fish assemblage are poorly known. Hence, we conducted an exhaustive literature review and a fieldwork in six coastal points of Argentina to update the species composition and determine the hierarchical structure of the fish assemblage. From the 206 species registered in the literature, 48 were not confirmed, 13 were absent, five were taken as synonymized species, 29 were supported by literature and 107 were confirmed; one was an established exotic species, and three were a non-established exotic species. The findings reported here suggest that the fish assemblage currently comprises 141 species, including four new records. Analysis of fieldwork data in number and weight of fish captured resulted in an assemblage hierarchical structure of five dominant, 22 frequent, and 45 rare species; 16 dominant, 11 frequent, and 45 rare taxa, respectively. These results could be used as baseline to monitor, manage, and preserve neotropical fish species in their southern distribution boundary.